ENGAGE: Guided Activity-Based Gaming in Neurorehabilitation after Stroke: A Pilot Study. (23rd April 2012) - Reinthal, Ann; Szirony, Kathy; Clark, Cindy; Swiers, Jeffrey; Kellicker, Michelle; Linder, Susan
Abstract : Introduction . Stroke is a leading cause of disability in healthy adults. The purpose of this pilot study was to assess the feasibility and outcomes of a novel video gaming repetitive practice paradigm, (ENGAGE) enhanced neurorehabilitation: guided activity-based gaming exercise. Methods . Sixteen individuals at least three months after stroke served as participants. All participants received concurrent outpatient therapy or took part in a stroke exercise class and completed at least 500 minutes of gaming. Primary baseline and posttest outcome measures included the Wolf motor function test (WMFT) and the Fugl-Meyer assessment (FMA). ENGAGE uses a game selection algorithm providing focused, graded activity-based repetitive practice that is highly individualized and directed. The Wilcoxon signed ranks test was used to determine statistical significance. Results . There were improvements in the WMFT (P = 0.003 ) and the FMA (P = 0.002 ) that exceeded established values of minimal clinically important difference. Conclusions . ENGAGE was feasible and an effective adjunct to concurrent therapy after stroke.